Peningkatan Kemampuan Komunikasi Matematis Siswa Melalui Model Pembelajaran CORE dengan Pendekatan Scientific - Ria Deswita; Yaya S Kusumah; Jarnawi A Dahlan (Edumatika : Jurnal Riset Pendidikan Matematika, 2018)
This research is motivated by the importance of mathematical communication ability. The mathematical communication ability of students is still low. In order that this problem can be solved, a learning model that can enhance mathematical communication ability of students is required. In this research, CORE model learning with a scientific approach was selected. This study aims to analyze the enhancement of mathematical communication ability. This research was a quasi-experimental with nonequivalent control group design. The population was students in eighth grade in one of the junior high schools in Jambi. The sample consisted of two classes which were selected by purposive sampling. The instrument of this research is a test of mathematical communication ability. The data were analyzed using the independent t-test. Based on the data analyzed, it is found that: The enhancement of mathematical communication ability of students who received the CORE learning model with the scientific approach is better than the enhancement of students who received conventional learning.